Jurnal Menu Variety, Price, And Service Quality Drive Catering Purchases: Keragaman Menu, Harga, dan Kualitas Layanan Menjadi Faktor Penentu dalam Keputusan Pembelian Jasa Katering - Damayanti, Diana Putri; Rusdianto, R. Yuniardi (Academia Open, 2026)
General Background: The catering industry has experienced significant growth driven by increasing demand for food services across various events, requiring businesses to adopt effective marketing strategies to attract consumers. Specific Background: Catering providers offer diverse menu options, competitive pricing, and service quality to meet customer preferences and support purchasing decisions. Knowledge Gap: Previous studies have reported inconsistent findings regarding the roles of menu variety and price in shaping purchasing decisions, necessitating further empirical investigation. Aims: This study examines the relationships between menu variety, price, and service quality and purchasing decisions at a catering business in Sidoarjo. Results: Using a quantitative causal comparative approach with 100 respondents and multiple regression analysis, the findings show that menu variety (β = 0.307; p = 0.007), price (β = 0.366; p = 0.001), and service quality (β = 0.358; p < 0.001) each demonstrate positive and significant relationships with purchasing decisions, both partially and simultaneously (F = 33.080; p < 0.001). Novelty: This study confirms the combined and individual roles of key marketing variables within a single empirical model in the catering context. Implications: The findings provide practical guidance for catering businesses to prioritize diversified menus, appropriate pricing, and improved service quality to support consumer purchasing decisions. Highlights: All examined variables show statistically significant positive relationships with consumer choices. Simultaneous testing confirms the combined role of marketing variables in decision formation. Regression results indicate consistent contributions across all independent factors. Keywords: Menu Variety, Price, Service Quality, Purchasing Decision